Konsep Manajemen Humas Pendidikan Dalam Meningkatkan Citra Madrasah di MI Muhammadiyah Tinggarjaya - Oepyt Risky Laelatuzzahro; Umi Halwati (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This study aims to find out how the concept of education public relations management at MI Muhammadiyah Tinggarjaya, functions of the concept of public relations management and also understands the duties of public relations in improving the image of madrasas. The research method used is a qualitative method, while the technique for collecting data in this study is using Library Research and interviews. While the results of the study show that the concept of public relations management and the task of public relations in improving the image of madrasas have been carried out well both from planning, organizing, implementing as well as evaluating. The public relations task of improving the image of the madrasa at MI Muhammadiyah Tinggarjaya has also been carried out which aims to establish good relations with the community and also to improve the good image of MI Muhammadiyah Tinggarjaya